Effect of Immersion Duration in Coffee Beverage on Colour Stability of Polymethyl Methacrylate Denture Base Reinforced with 1% Chitosan Nanogel (Laboratory Study) - Rahmawati, Lutfi; Dahar, Eddy; Angelia, Veronica (TALENTA, 2023)
Hot polymerized acrylic resin (RAPP) denture bases have several weaknesses, so RAPP requires reinforcing materials, one of which is chitosan. Extrinsic factors cause color changes in RAPP. The aim of this research was to determine the effect of soaking time for RAPP denture base material after adding 1% chitosan nanogel in coffee solution on color stability. Laboratory experimental research, using 16 cylindrical plates, diameter 15 x 2 mm (n = 8 from each group). There are 2 groups, the water-soaked group and the coffee drink group. Color stability measurements were carried out before and after soaking for 1, 2, 3, 4, and 7 days. The color stability of the samples was tested using a colorimeter and color changes were analyzed using the Kruskall-Wallis and Mann-Withney tests. There is an effect of soaking time for RAPP denture base material on color stability with a value of p = 0.0001. Soaking the RAPP denture base material after adding 1% chitosan nanogel in a coffee solution for color stability for 4 days is still clinically acceptable.